Stabilization of soil using Kenaf Fibre and Empty Fruit Bunch (EFB) in increasing compaction characteristics / Farah Hafifee Ahmad, Mazidah Mukri and Lannie Francis - Ahmad, Farah Hafifee; Mukri, Mazidah; Francis, Lannie (2024)
One of the most crucial and quite a huge challenge is the stabilization of the soils because it will affect long term strength and the geotechnical structures. Using waste material and natural fibre for improving soil properties is advantageous because they are cheap, locally available and eco-friendly. Currently, there are intensive studies on using Kenaf Fibre and Empty Fruit Bunch (EFB) to increase concrete strength in construction. However, there was a lack of studies on how Kenaf Fibre and EFB were used in soil stabilizing, especially in enhancing the compactness of the soil. This study aims to investigate the impact of adding the different percentages of kenaf fibre and EFB on maximum dry density (MDD) and optimum moisture content (OMC). Kenaf fibre and EFB with various percentages from 0,5,10,15 and 20% were used in this study. The optimum ratio that gives the highest value of maximum dry density (MDD) and optimum moisture content (OMC) is considered identical for stabilizing the soil.